2023
DOI: 10.1126/sciadv.adg5551
|View full text |Cite
|
Sign up to set email alerts
|

Radar remote sensing reveals potential underestimation of rainfall erosivity at the global scale

Qiang Dai,
Jingxuan Zhu,
Guonian Lv
et al.

Abstract: Rainfall kinetic energy (RKE) constitutes one of the most critical factors that drive rainfall erosivity on surface soil. Direct measurements of RKE are limited, relying instead on the empirical relations between kinetic energy and rainfall intensity ( KE-I relation), which have not been well regionalized for data-scarce regions. Here, we present the first global rainfall microphysics–based RKE ( RKE MPH ) flux retrieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…It has been shown that low and moderate intensities of fire will not directly affect the soil structure whereas, under severe fire generating high temperatures, organic matter and roots will decompose, exposing the inorganic soil, which alters the soil structure and results in soil compaction and hardening, thereby reducing the air permeability and water retention of the soil [20]. Rainfall is the primary driving force of soil erosion [21]. Vegetation and litter function to intercept and absorb rainwater [22,23].…”
Section: State Of the Artmentioning
confidence: 99%
“…It has been shown that low and moderate intensities of fire will not directly affect the soil structure whereas, under severe fire generating high temperatures, organic matter and roots will decompose, exposing the inorganic soil, which alters the soil structure and results in soil compaction and hardening, thereby reducing the air permeability and water retention of the soil [20]. Rainfall is the primary driving force of soil erosion [21]. Vegetation and litter function to intercept and absorb rainwater [22,23].…”
Section: State Of the Artmentioning
confidence: 99%
“…Studies have indicated that E values derived from 1-hourly in-situ precipitation data tend to underestimate those obtained from 1minute data by approximately 10% (Agnese et al, 2006;Yin et al, 2007). In 2023, Dai et al (2023) introduced the first global rainfall microphysics-based E, utilizing parameters retrieved from radar reflectivity. Compared to the radar remote sensing-based E values, the multi-year averaged annual rainfall kinetic energy calculating using E-I method was smaller with biases ranging from -6.17% to -12.5% across distinct regions worldwide.…”
mentioning
confidence: 99%